ASSESSING LEARNERS' INTERACTION QUALITY DURING DIGITAL STORY TELLING PROCESS - Yazid, M; Anwar, Khoirul; Arifani, Yudhi; Maruf, Nirwanto (Universitas PGRI Sumatera Barat, 2023)
This qualitative study delves into digital storytelling, focusing on the quality of interactions among learners engaged in this innovative pedagogical approach. This research aims to provide a comprehensive description of these interactions, analyze the outcomes, and critically evaluate the advantages and disadvantages of interaction quality in the context of digital storytelling. Through in-depth interviews and participant observation, we explored the experiences of 21 grade X students at MA Al-Aman in Lamongan, East Java. Thematic analysis of the collected data revealed that digital storytelling fosters collaborative engagement, allowing students to work together, share ideas, and co-create narratives. It enhances their understanding of subject matter, nurtures meaningful discussions, and fosters improved communication skills. The advantages of this approach far outweigh the recognized disadvantages, such as occasional disagreements and time constraints for collaboration. This research contributes to the educational discourse, emphasizing the profound impact of interaction quality on learning experiences. However, this study has limitations related to its scope and qualitative nature. Future research should explore diverse educational settings, digital storytelling tools, and pedagogical strategies. In conclusion, this study highlights the transformative potential of interaction quality in the context of digital storytelling, offering students a dynamic platform for collaboration, meaningful communication, and enriched learning experiences.